2021
DOI: 10.1101/2021.12.07.471547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The m6A reader YTHDF2 is a negative regulator for dendrite development and maintenance of retinal ganglion cells

Abstract: The precise control of growth and maintenance of the retinal ganglion cell (RGC) dendrite arborization is critical for normal visual functions in mammals. However, the underlying mechanisms remain elusive. Here we find that the m6A reader YTHDF2 is highly expressed in the mouse RGCs. Conditional knockout (cKO) of Ythdf2 in the retina leads to increased RGC dendrite branching, resulting in more synapses in the inner plexiform layer. Interestingly, the Ythdf2 cKO mice show improved visual acuity compared with co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 77 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…Immunostaining of Brn3a, AP2a and PKCa on the retinal vertical sections showed that generation of retinal ganglion cells, amacrine cells, or bipolar cells was not affected in the Ythdf1 scKO retinas at P6 and P15 (Figures S4B-S4F). These results and our previous findings (Niu et al, 2022) together suggest that knockout of Ythdf1 or Ythdf2 alone does not affect retinal neurogenesis.…”
Section: Double Knockout Of Ythdf1 and Ythdf2 Causes Cortical Neuroge...supporting
confidence: 88%
See 4 more Smart Citations
“…Immunostaining of Brn3a, AP2a and PKCa on the retinal vertical sections showed that generation of retinal ganglion cells, amacrine cells, or bipolar cells was not affected in the Ythdf1 scKO retinas at P6 and P15 (Figures S4B-S4F). These results and our previous findings (Niu et al, 2022) together suggest that knockout of Ythdf1 or Ythdf2 alone does not affect retinal neurogenesis.…”
Section: Double Knockout Of Ythdf1 and Ythdf2 Causes Cortical Neuroge...supporting
confidence: 88%
“…Gene Ontology (GO) analysis of those target mRNAs revealed enrichment of genes related to regulation of nervous system development, regulation of neuron differentiation, regulation of neurogenesis et al (Figures 7B,S7A,and S7B), which is consistent with the redundant functions of YTHDF1 and YTHDF2 in mediating m 6 A regulation of cortical neurogenesis. We have previously shown that anti-YTHDF2 RIP-seq in mouse retina identified 1638 mRNAs (Niu et al, 2022). We also carried out anti-YTHDF1 RIP-seq in mouse retina and identified 2969 mRNAs (Figure 7C and Table S2).…”
Section: Double Knockout Of Ythdf1 and Ythdf2 Causes Cortical Neuroge...mentioning
confidence: 81%
See 3 more Smart Citations